A Tendency of Synthesis in F. Schiller’s Aesthetics - Andrijauskas, Alfredas (Problemos, 1986)
The article deals with the two opposite types of creation in the naive and sentimental poetry of F. Schiller, namely, the realistic one and the idealistic one. The types are equally important for the German poet. Only the synthesis of both types leads to the perfection in creation.